دور المراجعة الداخلية فى استمرارية المنشأة: دراسة تطبيقية على شركات القطاع الخاص بمنطقة الجوف - محمد، عبدالرحمن عمر أحمد (جامعة الأزهر - مركز صالح كامل للاقتصاد الإسلامي, 2015)
تهدف هذه الدراسة إلى إبرا ز دور المراجعة الداخلية في استمرارية المنشأة في القطاع الخاص بمنطقة الجوف، باعتبار أن: المراجعة الداخلية مقياس مهم لتقييم أداء الشركات. والاعتماد على لوائح شفافة ضروري لضمان استمرارية المنشأة. ويتكون مجتمع الدراسة من المحاسبين والمراجعين الداخليين ل 20 منشأة، تعمل في النشاطات المختلفة بالإضافة إلى أعضاء هيئة التدريس من ذوي الاختصاص، حيث استخدمت العينة العشوائية. وتم توزيع: 60 قائمة استقصاء، وحللت :47 استمارة مستوفية باستخدام برنامج (spss) لمعالجة البيانات. ومن خلال التحليل فقد أبرزت الدور الفعال لعمليات التدقيق الداخلي في ديمومة المؤسسة لذا يوصي الباحث بايلاء هذه العملية الرعاية والاهتمام اللازم من قبل الإدارات العليا لما لها من أثر إيجابي في زيادة الإيرادات وتخفيض حجم الفاقد.
This research paper attempts to examine the role of internal auditing in «private sector firms operating in AL-JUOF province». As the internal auditing is an important tool for performance evaluation. Consequently, the reliability on transparent rules and regulations is essential to ensure the continuity of the firm. Our sample targets internal auditors of 20 firms belonging to different sectors in addition to faculty in the specialty. We analyzed 47 complete questionnaires out of 60 using SPSS program. First, we investigate whether the absence of the internal auditing in the firm impacts the loss of financial resources by private sector firms. Second, we study the impact of the absence of internal control systems on the value firms fixed assets. The main results highlight: Internal auditing is relevant in private sector firms. The development of internal control systems protects the firms, assets. The necessity to introduce methods improving the efficiency and effectiveness of internal control systems is susceptible to ensure the continuity of the firm.
Keywords: المراجعة الداخلية -- الرقابة المالية -- مراجعة الحسابات